Analisis Bibliometrik Energi Angin dalam Sistem Energi Berkelanjutan Identifikasi Tren, Kolaborasi Ilmiah dan Research Gap - Putri Najiha; Arifa Putra Pratama; Andi Pratama Solin (Program Studi Teknik Industri Fakultas Teknik Universitas Islam Makassar, 2026)
This study aims to analyze the development of wind energy research within sustainable energy systems using a bibliometric approach. Data were collected from the Scopus database, comprising 2000 documents published between 2021 and 2026, and analyzed Bibliometrix (RStudio) and VOSviewer. The results indicate a significant upward trend in publications, reflecting growing global interest in wind energy as part of the energy transition. The conceptual structure is dominated by technical topics such as wind power and wind turbines, but is gradually shifting toward data-driven approaches, including machine learning and wind forecasting. Additionally, integrative themes such as energy storage and hybrid systems highlight the transition toward more complex energy systems. Collaboration analysis reveals the dominance of developed countries, although participation from developing nations is increasing. This study identifies gaps in multidisciplinary integration and the comprehensive application of intelligent technologies in wind energy research.